Factores asociados a aborto en el Hospital de Yantzaza en Zamora en el periodo diciembre 2015-diciembre 2016. - Herrera Sarango, Stephany Catherine (2017)
This research work was conducted at the Yantzaza Hospital in order to determine which factors influence on how frequent abortions occur. The study was aimed to determine the frequency of abortion on young and adult patients, to identify the pre-existing factors for abortion in adult and young patients, and to establish the most frequent symptoms and complications in patients who have suffered an abortion. This study is quantitative, descriptive and retrospective. Clinical records were studied and data was collected in a graph which included all variables. It was tabulated using the program Excel 2013. From a 120 pregnant women population, a sample of 42 patients with abortion diagnosis was obtained. Patients with clinical and ultrasound abortion di agnosis before reaching 20 weeks were included; however, pregnant patients without abortion diagnosis were excluded. Young patients aged 14 to 25 years had a higher abortion rate with a 28.6% (n = 12). The main factor was injuries (incidental falls) with a 33.3% % (n = 14). Abdominal pain located in the hypogastrium was the most frequent symptom with a 59.5% (n = 25), followed by genital bleeding with a 37%. After an abortion, in a 76% (n = 32) of most patients, medical problems were not reported; on the other hand, bleeding and infections appeared, but in a lower percentage. Key words: factors, abortion, adult, young.